Recurrent goitrous transformation and postoperative hypothyroidism — the arguments to execution of organ-preserving thyroid sergery - A. N. Galyan; O. S. Popov; V. I. Tikhonov; V. D. Zavadovskaya; S. N. Gasparyan; V. V. Udut (Бюллетень сибирской медицины)
The study included 557 patients with diffuse nodular colloidal goiter and different functional state of thyroid gland after routine surgeries. In the postoperative period was diagnosed hypothyroidism and in its presence the relapse nodulation in thyroid residue. In order to prevent the development of postoperative hypothyroidism, organopreserve surgical methods of the local cryodestruction of pathologic area thyroid gland and autotransplantation of intact thyroid tissue were suggested.